HUBUNGAN KECERDASAN EMOSIONAL DENGAN PERILAKU CARING PADA MAHASISWA KEPERAWATAN D3 STIKES HARAPAN BANGSA PURWOKERTO - Tri Sumarni (Universitas Harapan Bangsa Purwokerto, 2016)
Concept of caring mentioned much in nursing practice, but rarely defined in the context of nursingeducation. The establishment and maintenance of caring behavior is important to set up the timeof learning in the lecture bench. Caring behavior of students in the learning process is importantbecause it can make the students become confident and caring can apply to their peers, as a basisfor caring for patients when it works. Formation of caring behavior is influenced by many factors,one of which emotional intelligence. The purpose of this study to analyze the relationship between emotional intelligence and caringbehavior D3 Nursing student.This research is a quantitative observational with cross sectional design with a sample of 182 D3Nursing student. Sampling with a total sampling. The research instrument was a questionnaire. Analysis to test the hypothesis between independent and dependent variables with Pearson productmoment.Emotional intelligence research results averaged 48.64 with SD 5.36; for caring behavior anaverage of 35.96 with 3.121 SD; there is a relationship between emotional intelligence and caringbehavior (p value 0.000). Keywords: Emotional Intelligence, Caring Behavior Nursing Student